2014
DOI: 10.1002/lary.24973
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of findings obtained on 3DFLAIR MR imaging in patients with Ramsay‐Hunt syndrome

Abstract: RHS shows frequent abnormalities of IE or CN-VIII, as well as CN-VII on pre-/postcontrast 3D-FLAIR images. Precontrast hyperintensity of IE/CN-VIII on 3D-FLAIR is significantly correlated with the severity of facial palsy, the presence of vertigo, and the degree of hearing impairment but not with clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 25 publications
1
13
0
2
Order By: Relevance
“…Instead, the few post-mortem studies performed have shown various findings including none to mild inflammation of the geniculate ganglion, perivascular inflammation, demyelination and axonal loss along the facial nerve (Denny-Brown et al, 1944;Guldberg-Moller et al, 1959;Blackley et al, 1967;Aleksic et al, 1973). In addition, MRI examinations have revealed abnormalities localized not only to the inner ear and vestibulocochlear nerve, but also to the facial nerve (Brandle et al, 1996;Chung et al, 2015). The intratemporal facial nerve including the geniculate ganglion seems to swell in the acute phase of RHS, which has been observed during subtotal decompression surgery (Honda et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the few post-mortem studies performed have shown various findings including none to mild inflammation of the geniculate ganglion, perivascular inflammation, demyelination and axonal loss along the facial nerve (Denny-Brown et al, 1944;Guldberg-Moller et al, 1959;Blackley et al, 1967;Aleksic et al, 1973). In addition, MRI examinations have revealed abnormalities localized not only to the inner ear and vestibulocochlear nerve, but also to the facial nerve (Brandle et al, 1996;Chung et al, 2015). The intratemporal facial nerve including the geniculate ganglion seems to swell in the acute phase of RHS, which has been observed during subtotal decompression surgery (Honda et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…63 Prognosis for hearing was not good in ears with a high signal on precontrast 3D-FLAIR. 65,66 Inflammation A signal increase in the labyrinthine fluid on 3D-FLAIR in various inflammatory diseases such as acute meningitis, acute otitis media, Wegener's granulomatosis, 27 mumps deafness, 26 RamsayHunt syndrome, [67][68][69] and labyrinthine fistula by a cholesteatoma 70 has been reported. Signal increase in the labyrinthine fluid on precontrast 3D-FLAIR suggests the presence of a small degree of hemorrhage or protein, and on post-contrast 3D-FLAIR, enhancement of the labyrinthine fluid suggests the active breakdown of the blood-labyrinthine barrier.…”
Section: Visualization Of White Matter Tractsmentioning
confidence: 99%
“…For RHS, it has been suggested that the vestibular nerve and/or labyrinth are involved in the accompanying dizziness [ 9 ]. A three-dimensional fluid-attenuated inversion recovery magnetic resonance imaging (MRI) study revealed that the pre-contrast hyperintense signal in the cochlea, vestibule, and the vestibulocochlear nerve of RHS patients was correlated with presence of dizziness [ 10 ]. In addition, the different aspects of vestibular impairment and recovery were compared between RHS and other inner ear diseases such as vestibular neuritis (VN) or sudden deafness with vertigo [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%